2022
DOI: 10.1111/jsr.13695
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep and wakefulness in the recognition of emotional pictures

Abstract: Sleep has a beneficial effect on memory consolidation. However, its role in emotional memory is currently debated. Here, we investigate the role of sleep and a similar period of wakefulness on the recognition of emotional pictures and subjective emotional reactivity. Forty participants without any major physical, neurological or psychological condition were randomly assigned to the Sleep First Group or Wake First Group. The two groups underwent the encoding phase of an emotional images task with negative and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…While the content is preserved over periods of sleep, the affective tone should start to decline after a sleep period. However, it is in line with the idea that sleep tends to preserve the emotional reactivity associated with an emotional event [ 49 ] and in line with previous empirical studies using subjective reports [ 50 , 51 , 52 , 53 , 54 ]. Interestingly, the current sample showed no difference in terms of arousal for neutral and positive stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…While the content is preserved over periods of sleep, the affective tone should start to decline after a sleep period. However, it is in line with the idea that sleep tends to preserve the emotional reactivity associated with an emotional event [ 49 ] and in line with previous empirical studies using subjective reports [ 50 , 51 , 52 , 53 , 54 ]. Interestingly, the current sample showed no difference in terms of arousal for neutral and positive stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…As noted above, the sleep effect was strongly diminished in the wake-first group compared to the sleep-first condition, suggesting that sleep may have less of an impact on emotional memory processing once the memory reaches this stage, at least for some paradigms. A final study recently utilized a similar sleep-first vs. wake-first protocol, but memory was tested for negative and neutral scenes on three separate occasions across the protocol: immediately following encoding, 12-h after encoding, and 24-h after encoding ( Carollo et al, 2022 ). While immediate testing showed no differences, at the 12-h mark memory was clearly benefited by a sleep period, though this effect was generalized and not limited to negative pictures.…”
Section: Sleep Placement and Emotional Memory Processingmentioning
confidence: 99%
“…While immediate testing showed no differences, at the 12-h mark memory was clearly benefited by a sleep period, though this effect was generalized and not limited to negative pictures. Interestingly, testing after the 24-h delay showed that the sleep-first group showed deterioration in memory in the subsequent 12-h of wakefulness, while memory was largely preserved from the 12- to 24-h test in the wake-first group after receiving their opportunity for sleep in the second half of the protocol ( Carollo et al, 2022 ). Importantly, while the authors clearly state that the intention was to assess delayed sleep-dependent consolidation on emotional memory, it is likely that the 12-h testing session reactivated memory traces for the stimuli that had been set aside for the 24-h assessment.…”
Section: Sleep Placement and Emotional Memory Processingmentioning
confidence: 99%